Modelling of the deformation‐dependent fluid flow in the fibrous gas diffusion layer of fuel cells. Issue 1 (15th March 2018) - Chaaban, Mohamad; Heider, Yousef; Markert, Bernd
Abstract: The following contribution presents a numerical model for the description of the compression of gas diffusion layers (GDL) of polymer electrolyte membrane fuel cells (PEMFC). Proceeding from a macroscopic multiphasic modelling approach for porous materials, the work below instills the neo‐Hookean material law of finite deformations within the framework of the theory of porous media (TPM). Subsequently, the alteration in the deformation‐dependent intrinsic permeability is computed as an evaluation criteria of the effect of compression on the performance of the GDL. In furtherance of the affected transport property, a modified intrinsic permeability function is presented and validated to fit the profile of compression. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)